2017
DOI: 10.1002/masy.201700018
|View full text |Cite
|
Sign up to set email alerts
|

The Manifold Varieties of Poly(2‐Hydroxyethyl Methacrylate) Hydrogels−IPNs

Abstract: Summary The interpenetrating network structure was used to control mechanical properties of hydrogels based on poly(2‐hydroxyethyl methacrylate) (PHEMA) (first network (A) or second network (B)) and poly(glycerol methacrylate) (PGMA) (network B). In order to understand the structure, mechanical and swelling properties of sequentially made IPN hydrogels, the swollen PHEMA network microstructure and its formation was investigated by means of swelling and SWAXS experiments. Visually clear and microscopically homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…For proper application in these fields, morphology of hydrogels must be precisely controlled. It can be done through varying the ratio of components in the reaction mixture [24]: for example, certain excess of diluent can trigger pore formation during polymerization by reaction induced phase separation [19]. For example, lightly crosslinked systems based on PHEMA undergo the phase separation above the critical amount of water about 40-45 vol.% [3,20,25].…”
Section: Introductionmentioning
confidence: 99%
“…For proper application in these fields, morphology of hydrogels must be precisely controlled. It can be done through varying the ratio of components in the reaction mixture [24]: for example, certain excess of diluent can trigger pore formation during polymerization by reaction induced phase separation [19]. For example, lightly crosslinked systems based on PHEMA undergo the phase separation above the critical amount of water about 40-45 vol.% [3,20,25].…”
Section: Introductionmentioning
confidence: 99%
“…The original DN hydrogels comprised two interpenetrating, chemically cross‐linked hydrogels, the first of which was fragile and highly swollen because it was a rather densely cross‐linked polyelectrolyte, and the second was nonionic, ductile and loosely cross‐linked . Subsequently, however, the DN concept was expanded and proven to also hold when the order of the polyelectrolytic and nonionic components was reversed, when one or both networks were physically rather than chemically cross‐linked, and even when both networks were nonionic . In all cases, the mechanical properties (stress and strain at break, Young's modulus) of the final DN hydrogels were better than those of the two individual components separately.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 Subsequently, however, the DN concept was expanded and proven to also hold when the order of the polyelectrolytic and nonionic components was reversed, when one or both networks were physically rather than chemically cross-linked, and even when both networks were nonionic. 13,14 In all cases, the mechanical properties (stress and strain at break, Young's modulus) of the final DN hydrogels were better than those of the two individual components separately. Furthermore, in most of the studies on DN hydrogels to date, the two constituting networks were poorly defined, as they were prepared via conventional free radical cross-linking copolymerization chemistries, employing photochemical or thermal initiation.…”
mentioning
confidence: 96%
“…One of the first hydrogels successfully applied as biomaterial is PHEMA . Initially, it was envisioned for contact lenses in the 60's and later for rhinoplasty .…”
Section: Introductionmentioning
confidence: 99%
“…The major improvements were achieved by introduction of 1%–2% BC; compared with neat gels, the storage shear modulus (G) increased by a factor of 4–5 in the case of PHEMA hydrogels. Dušková‐Smrčková et al used another strategy for the mechanical enhancement of PHEMA hydrogels, the preparation of interpenetrating polymer networks (IPN) of PHEMA of different porosities (network A) with poly(glycerol methacrylate) (network B) . Results showed that, in most cases, an increase of tensile moduli and improvement of ultimate tensile properties was achieved.…”
Section: Introductionmentioning
confidence: 99%